THE FORMING OF PRODUCTIVITY IN SPRING BARLEY VARIETIES IN THE DRY STEPPE ZONE OF VOLGOGRAD PROVINCE - G. V. Kozubovskaya; O. Y. Kozubovskaya; V. I. Balakshina (Труды по прикладной ботанике, генетике и селекции)
The results of comparative evaluation of productivity are presented for 24 spring barley cultivars of various genotypes from VIR’s collection with regard to the climate conditions of their cultivation. In the dry steppe zone of Volgograd Province considerable differences have been observed in the productivity and yield components depending on climate factors and genotypes. Five accessions with high adaptability ratios have been identified as well as several cultivar accessions with high 1000 grain weight manifested in different years of growing.